2019
DOI: 10.1177/0049475519887654
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day postoperative outcome of patients with non-traumatic gastroduodenal perforations in southwestern Uganda

Abstract: We studied our 30-day postoperative outcomes in patients with non-traumatic gastroduodenal perforation (NTGDP) in Mbarara Regional Referral Hospital, southwestern Uganda. We conducted a one-year prospective study of patients who underwent exploratory laparotomy for suspected NTGDP between June 2016 and July 2017. Twenty-nine patients had NTGDP, the male-to-female ratio was 3:1 and median age was 60 years (range = 13–80 years). Most (83%) patients were negative for Helicobacter pylori on histology. One patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Studies by Pescatore et al [7] and Tokunaga et al [8] showed the highest H. pylori prevalence among patients with GDP and ranged from 92% to 100% (n = 119 patients), compared to the other studies that showed a prevalence of infection between 20 and 84.6% (n = 1457) [9][10][11][12][13][14][15][16]. Two of the studies reported the lowest prevalence of H. pylori infection, with 12.5% among a total number of 48 patients and 13.8% among 29 patients with a perforated peptic ulcer, which could be due to the small sample size of both studies [3,17]. 2020) [3] The association between H. pylori and a perforated gastroduodenal ulcer.…”
Section: The Prevalence Of H Pylori Infection Among Patients With Gas...mentioning
confidence: 87%
“…Studies by Pescatore et al [7] and Tokunaga et al [8] showed the highest H. pylori prevalence among patients with GDP and ranged from 92% to 100% (n = 119 patients), compared to the other studies that showed a prevalence of infection between 20 and 84.6% (n = 1457) [9][10][11][12][13][14][15][16]. Two of the studies reported the lowest prevalence of H. pylori infection, with 12.5% among a total number of 48 patients and 13.8% among 29 patients with a perforated peptic ulcer, which could be due to the small sample size of both studies [3,17]. 2020) [3] The association between H. pylori and a perforated gastroduodenal ulcer.…”
Section: The Prevalence Of H Pylori Infection Among Patients With Gas...mentioning
confidence: 87%
“…The fluid prescriptions that follow, will be according to fluid balance chart. Other post-operative instructions will include; IV ceftriaxone 2g once a day (OD) for 5 days, IV metronidazole 500mg 8 hourly for 5 days, IV Omeprazole 40mg OD till oral feeding is initiated, IV Paracetamol 1g 8 hourly till oral feeding is initiated, Oral warm water will be started on first POD, early removal of NGT will be done, ambulation will be encouraged from first POD [ 14 25 ]. In addition to the above, patients in group A will receive chewing gum and below is a clear instruction on how they will use it.…”
Section: Methodsmentioning
confidence: 99%
“…ERAS protocols have been proven to reduce POI duration in elective surgeries but data about such protocols in emergency surgeries is lacking [ 24 ]. The elements of ERAS recommended for reduction of POI in emergency surgeries, have been based on law risk patients [ 5 24 ], yet most of the patients in resource limited countries present late with a high risk of peritonitis and morbidity [ 25 ]. More so, some doctors avoid early feeding in fear of the complications since up to 20% of the patients do not tolerate it [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary peritonitis is associated with complications such as surgical sites infection, bust abdomen, re-laparotomy, prolonged hospitalization, morbidity and mortality (2,7).…”
Section: Introductionmentioning
confidence: 99%